Effectiveness Analysis of Government Livestock Assistance in Increasing Livestock Population in Humbang Hasundutan Regency, Indonesia - Sanggam K. Sihombing; Charloq; Achmad Siddik Thoha (Archives of Current Research International, 2024)
This research employs a qualitative approach to explore in-depth insights into the implementation of the government livestock assistance program in Humbang Hasundutan Regency. Through this approach, data is obtained from field observations, interviews with recipient farmers, and a review of documents related to program implementation. Data analysis involves delineating the program’s implementation stages, identifying inhibiting factors, and evaluating the program’s impact on livestock populations and the welfare of farming communities. The findings indicate that, despite the well-executed stages of distribution, counseling, mentoring, and monitoring/evaluation, the livestock assistance program has not been effective in increasing the livestock population. Community empowerment, the main goal of the program, is hindered by the lack of skills among selected livestock aid recipients. As a recommendation, the study suggests that local governments conduct more selective verification and selection of prospective aid recipients to make the program more effective and targeted. Aid recipients are also advised to be consistent in livestock maintenance according to the technical guidance of the relevant department and enhance their understanding of proper livestock farming practices. This study contributes to a better understanding of the implementation of livestock assistance programs at the local level and offers guidance for improving policies and the implementation of similar programs in the future.